Implementation of One-Roof School Management (Multi-Case Study in Kema District, North Minahasa Regency) - Da’u, Sitti Aisah; Lengkong, Jeffry S. J.; Krowin, Marthinus (Journal of Social Research, 2023)
Implementation of One Roof School Management is one of the government's policies to provide educational services in remote, isolated, and scattered areas. This effort is intended to provide opportunities for the entire community to enjoy education even in areas that are difficult to reach. Using a qualitative descriptive method, research was conducted to obtain an in-depth picture of the implementation of One Roof School management at the Pimpin Small Public Elementary School and Satap Pimpin Middle School. Information was collected using observation techniques, interviews, and document studies with the research instrument being the researcher himself, the results of the analysis obtained were that the implementation of one-roof schooling at SD Negeri Kecil Pimpin and SMP Negeri Satu Atap Pimpin involved a pattern of two managers, careful planning, and collaboration between elementary and middle school teachers. Obstacles faced include a shortage of teachers in junior high schools, teacher qualifications that do not meet standards, administrative staff who are not professional, limited funds, and minimal participation from parents and the community. Based on the conclusions, it is recommended that all stakeholders continue to improve their performance and active participation. Teachers who do not meet the qualification requirements are advised to pursue higher education. The education department has been asked to increase teacher professional development activities, the North Minahasa Regency government needs to pay attention to the placement of teachers and administration, as well as provide additional operational costs for schools in remote areas. The community is also expected to support the implementation of one-roof schools by increasing active participation, especially in efforts to meet school operational needs.